Henrik Ibsen’s a Doll’s House as a Feminist Play - Kaur, Rajpal (International Journal For Research In Educational Studies, 2016)
Henrik Ibsen was a prominent poet and dramatist of nineteenth century. He wrote many plays for the social cause. A Doll’s House is also one of his influential plays, in which he raised a voice in favour of women. He sought equality for men and women, which he subsequently presented in this play through the character of Nora Helmer. The paper aims to analyse the play on feminist grounds. In this play, Nora seeks individuality and autonomous selfhood, which she acquires on terms of breaking the shackles of gender roles of mother and wife.